Osteomyelitis and extensor tenosynovitis- an unusual presentation of Neisseria gonorrhoeae. (2020) - Anwar, Shamsuddin; Acharya, Sudeep; Shahab, Asna; Glaser, Allison
Abstract: Disseminated gonococcal infection (DGI) commonly presents with arthritis, flexor compartment tenosynovitis, and dermatitis. Osteomyelitis and extensor compartment tenosynovitis caused by DGI is rarely reported in medical literature. We describe one such case of extensor tenosynovitis and osteomyelitis of the wrist joint which symptomatically improved after arthrotomy and intravenous antibiotics.